DIGITAL SHIELD: THE PROTECTIVE ROLE AGAINST HUMAN RIGHTS VIOLATIONS IN CYBER INTERVENTIONS - Demir, Muhammet Ali (Cyberpolitik Journal, 2026)
Atrocity crimes represent some of the most severe violations of international order and are primarily addressed within the framework of humanitarian intervention and the Responsibility to Protect (R2P). Traditional military interventions have been widely criticized due to their potential infringement on state sovereignty and the high risk of operational failure, whereas emerging digital technologies have introduced cyber humanitarian intervention as a possible alternative. The aim of this article is to explore the potential of cyber operations in preventing or halting mass atrocity crimes within the context of R2P and to critically assess the legal, ethical, and practical constraints of this approach. Methodologically, the study adopts a normative analytical framework, drawing on international law, cybersecurity, and humanitarian intervention scholarship to establish a conceptual and legal basis. Existing literature tends to focus predominantly on military or diplomatic means of intervention, with only limited engagement with the notion of cyber humanitarian intervention. This gap highlights the need for a comprehensive assessment of how cyber measures align with international law, their feasibility, and associated risks. The findings suggest that cyber interventions may support the implementation of R2P by safeguarding access to information, protecting communication infrastructures, and limiting the digital capacities of perpetrators. Nevertheless, the approach also entails significant limitations, particularly concerning state sovereignty, attribution challenges, the lack of international cooperation, and ethical accountability. In conclusion, while cyber humanitarian intervention does not constitute a definitive solution on its own, it can be considered a complementary tool for enhancing the effective realization of the R2P principle.